Occurrences of Indigestible Foreign Bodies in Cattle Slaughtered at Morogoro Municipal Slaughterhouse, Tanzania. (22nd February 2018) - Bwatota, S. F.; Makungu, M.; Nonga, H. E.
Abstract : A cross-sectional study was conducted to determine the occurrence of indigestible foreign bodies (IFB) in cattle slaughtered at Morogoro Municipal Slaughterhouse, Tanzania. A total of 387 slaughter cattle were examined for presence of IFB. Out of 387 examined cattle, 93 (24.03%) had IFB in their forestomachs. The observed IFB were plastic bags, fruit seeds, clothing materials, ropes, hairballs, leather materials, stones, metallic nails, and wire. Plastic bags were the most frequently (50.5%) observed IFB followed by fruit seeds (18.3%). A significantly (p < 0.05 ) high proportion of old animals (31.7%) had IFB compared to the young animals (21.2%). Similarly, the frequency of occurrence of IFB was significantly high (p < 0.05 ) in crossbred dairy cattle (42.3%) compared to local breeds (22.7%). Cattle that appeared with poor body condition (37.8%) were found to be more affected (p < 0.05 ) by IFB than those with good body condition (15.9%). In 91.4% of animals which had IFB, all the materials were located in the rumen. This study showed that presence of IFB is a common problem in cattle slaughtered at Morogoro Municipal Slaughterhouse and may significantly cause poor production and mortality in affected animals. Therefore, appropriate solid waste disposal should be implemented.